Minute bodies the intimate world of F. Percy Smith - Ott, Christine 1963-; Belhom, Thomas 1969- (BFI, 2017)
"This meditative, immersive film from Stuart A Staples and David Reeve is a tribute to the astonishing work and achievements of naturalist, inventor and pioneering filmmaker F Percy Smith. Smith worked in the early years of the 20th century, developing various cinematographer and micro-photographic techniques to capture nature's secrets in action Minute Bodies is an interpretative edit that combines Smith's original footage with a new contemporary score to create a hypnotic, alien yet familiar dreamscape that connects us to the sense of wonder Smith must have felt as he peered through his own lenses and saw these micro-worlds for the first time." [amazon.cu.uk]
Original: Großbritannien 2016
Bildformat 1.33:1
Special features: presented in high definition and standard definition ; a selection of films encapsulating the genius and art of F. Percy Smith ; illustrated booklet with full film credits and essays by Bryony Dixon, Tim Boon and Stuart A. Staples